Oxygen diffusion through air–water free surfaces in a pump–turbine operating in condenser mode. (March 2019) - Vagnoni, E.; Andolfatto, L.; Guillaume, R.; Leroy, P.; Avellan, F.
Highlights: Air diffusion is investigated to understand and predict air losses in a reversible pump–turbine. A theoretical framework is developed to model the gas diffusion. Oxygen concentration measurements validate the model and gas diffusion coefficients are computed. Air losses strongly depend on the densimetric Froude number, pressure and cooling discharge. Abstract: The present research aims at understanding the mass transfer of air into water in a reversible pump turbine operating in condenser mode. In particular, the diffusion of oxygen through the water free-surface both in the vaneless gap between the impeller blades and the closed guide vanes and in the cone of the draft tube is investigated. A theoretical framework is carried out to compute the diffusion equation describing the oxygen diffusion process in the investigated machine. Oxygen concentration measurements together with temperature and wall pressure measurements are performed to validate the theoretical model of the mass transfer of oxygen in the water volume and to evaluate the influence of the densimetric Froude number, of the gauge pressure and of the cooling discharge on the diffusion process. Moreover, the analytical solution of the diffusion equation applied to both the free surfaces in the vaneless gap and in the cone of the draft tube allows computing the global diffusion coefficient for each air–water free-surface. The results show that the oxygen concentrations computed by the analytical model of the oxygen diffusion are in agreement with the measurements. The dependency of the oxygen concentration in water on the densimetric Froude number, on the gauge pressure and on the water cooling discharge is also observed. The computed global diffusion coefficients are mainly dependent on the densimetric Froude number in the vaneless gap and in the cone of the draft tube. Finally, the results achieved allow estimating the air losses correlated to the oxygen diffusion causing the increase of the water level in the cone of the draft tube.